Functions of Code Switching: A Case Study - Muhammad Malek, Othman (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2015)
This is a case study which aims at delving into finding the reasons for code switching to Turkish, prevalent first language, in ELT classes as perceived by both teachers and students. It also aims at investigating whether there is a correlation between the students' and teachers' reported reasons. The study was conducted at the department of ELT, Eastern Mediterranean University (EMU), in Turkish Republic of Northern Cyprus. In the light of these aims, the study involved 50 Turkish speaking students from the first, second, third and fourth years studying in the bachelor program. In addition, 9 Turkish speaking teachers in the same program have participated to provide the information necessary for the study. Both quantitative and qualitative methods were employed to obtain the data for the study by utilizing a Likert-Scale questionnaire for students and semi-structured interviews for teachers. The study revealed that students and teachers reported different reasons for code switching to Turkish. By adopting Apple and Muyskn's (2006) model for functions of code switching, these reasons were categorized under different functions. According to the teachers' feedback in the interviews, they confirmed code switching for 6 functions: expressive, directive, referential, phatic, poetic and linguistic, whereas students reported code switching for 4 functions, based on the questionnaire: expressive, directive, referential, and poetic. By cross-checking the findings gained from the participants, there appeared to be significant consensus among the reasons for which they code switching. ÖZ: Bu örnek olay incelemesi, İngiliz Dili Eğitimi Bölümü’ndeki öğretmen ve öğrencilerin anadilleri olan Türkçe’de düzenek değiştirme nedenlerini bulmayı amaçlamaktadır. Bunun yanısıra bu çalışmada öğrenci ve öğretmenlerin sunduğu nedenler arasındaki bağlantı da incelenmiştir. Araştırma, Kuzey Kıbrıs Türk Cumhuriyeti, Doğu Akdeniz Üniversitesi, İngiliz Dili Eğitimi Bölümü’nde yapılmıştır. Bu amaçlar ışığında araştırmaya Lisans programının birinci, ikinci, üçüncü ve dördüncü sınıflarında okuyan ve Türkçe konuşan 50 öğrenci katıldı. Ayrıca, çalışma için gerekli bilgileri almak adına aynı programda olan ve Türkçe konuşan 9 öğretmen de katıldı. Araştırmada gerekli bilgilerin toplanması için Nitel ve Nicel metodlar kullanılmıştır, öğrenciler için Likert tipi anket ve öğretmenler için ise yarı yapılandırılmış görüşme kullanılmıştır. Araştırma öğrenci ve öğretmenlerin farklı nedenlerden dolayı Türkçe’de ‘düzenek değiştirme’ yaptığını ortaya koymuştur. Apple ve Muyskn’in (2006) düzenek değiştirme modelinin işlevlerini de ele alırsak, ortaya çıkan sebepleri farklı işlevler altında kategorize edebiliriz. Görüşmelerde, öğretmenlerin verdiği yanıtlara göre ‘düzenek değiştirme’yi 6 sebeple kullanıyorlar; etkilemek, direktif vermek, referans vermek, şiirsel ve dilbilimsel. Öğrenciler ise 4 nedeni rapor etmiştir; etkilemek, direktif vermek, referans vermek ve şiirsel. Katılımcılardan kazanılan fikirleri çapraz kontrol ettiğimizde ‘düzenek değiştirme’ için çok önemli bir fikir birliğinin ortaya çıktığını görebiliriz.
Master of Arts in English Language Teaching (ELT). Thesis (M.A.)--Eastern Mediterranean University, Faculty of Education, Dept. of English Language Teaching, 2015. Supervisor: Assoc. Prof. Dr. Javanshir Shibliyev.
Keywords: English Language Teaching; Code switching (Linguistics); English Language; Code switching; ELT classes; functions of code switching; typology of code switching; positive and negative attitudes